ANALISIS PENGARUH WAKTU PELAPISAN NIKEL PADA MATERIAL ALUMINIUM SERI 2024 TERHADAP KEKUATAN TARIK DAN KEKERASAN DENGAN METODE ELEKTROPLATING - Galang Anugrah Pratama Galang; Sehono; Ferry Setiawan (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
At this time the use of aluminum is already applied in the fields of industry, otomototif, and health. The use of aluminum cannot be separated from the good corrosion-resistant properties and has relatively good mechanical strength. In addition, aluminum is also easy to carry out the fabrication process. Such properties of aluminum can be applied to the manufacture of parts on aircraft. One type of aluminum that is widely used in aircraft is aluminum alloy 2024. To make the aluminum material better, one of the methods that can be used to make the aluminum material better is electroplating. The electroplating process is the transfer of the coating metal ions to the metal to be coated. The working principle of electroplating is that the anode will conduct ions to the cathode. In this study, an electroplating process was carried out by coating aluminum 2024 using nickel. The variations used in this study are the electroplating process time on the material, while the variations used are 20 minutes, 30 minutes, and 40 minutes. After the electroplating process is carried out, it then performs tensile and hardness testing on the material. From the results of tensile testing, for variations of aluminum without an electroplating process, it is the highest, as for the tensile strength value, which is 482.65 MPa. While in materials with the longest electroplating process (40 minutes) the tensile strength is 410,408 MPa. The hardness test also shows that the longer the electroplating process will reduce the hardness value